PENGARUH KARAKTERISTIK CORPORATE GOVERNANCE TERHADAP EFFECTIVE TAX RATE (ETR) (STUDI EMPIRIS PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI TAHUN 2011-2013) - Rahati Wulansari; Raja Adri Satriawan; Julita - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to examine the influence of Corporate Governance Characteristic consisting of Independent Commissioner, Audit Committee, Institutional ownership, and management ownership on the Effective Tax Rate (ETR). This study is an empirical research with the purpose of sampling techniques in data collection. Secondary data obtained from financial statement bank enterprises listing on the Stock Exchange during the year 2011 to the year 2013. Multiple regression analysis was conducted using SPSS version 17.00 for windows. The result of this study that the variables that affect the effective tax rate is independent commissioner, audit committee, and ownership of manajerial. While variable that did not affect the effective tax rate is institutional ownership.Keywords: Effective tax rate, Independent Commissioner, Audit Committee, Institutional Ownership, and Management Ownership.